The Congo Basin forests in a changing climate: policy discourses on adaptation and mitigation (REDD+) - Somorin, O.A.; Brown, H.C.P.; Visseren-Hamakers, I.J.; Sonwa, D.J.; Arts, Bas; Nkem, J. (2011)
This paper discusses the discourses on climate change adaptation and mitigation that are currently at the forefront in the Congo Basin. On mitigation, the forests have enormous opportunities to contribute to the reducing emissions from deforestation and forest degradation (REDD+) mechanism. But the forest itself and its multiple dependent societies and sectors need to adapt to potential climate risks. Hence, actors are debating the design of climate change policy in the forest sector. Theoretically, we combine the agency-focus of frame analysis and discourse theory to analyze how different agents hold frames on climate change adaptation and mitigation policies in the region. This paper draws upon interviews with 103 different actors from government, international organizations, non-governmental organizations, research institutions and private sector in three countries: Cameroon, Central African Republic (CAR) and Democratic Republic of Congo (DRC). Three discourses were found on policy response to climate change in the forest sector: mitigation policy only, separated policy on adaptation and mitigation, and an integrated policy on adaptation and mitigation. The various frames articulated around each discourse by the coalitions include elements of: costs and benefits, scale of operation, effectiveness, financial resources and implementation mechanisms. Overall, the mitigation discourse, through its mix of actors, resources and interests seems to be stronger than the adaptation discourse. The paper finally outlines a number of implications of the discourses for policy design.